PURPOSE A SACRED ROOM OF CHRUCHES BY PASTOR MANGUNWIJAYA CASE STUDY: CHURCH OF MARIA ASSUMPTA KLATEN, CHURCH OF THERESIA SALAM, AND CHURCH OF MARY - Tanumihardja (Jurnal Riset Arsitektur, 2018)
Abstract- Sacred space is everywhere and has become the part of human’s life since thousand years ago. One manifestation of the sacred space is the Catholic Church. A sacred space in the Catholic Church should be able to accommodate liturgical activities in accordance with the rules and the order of their activities so the celebration of the Eucharistic liturgy can run well. This study will attempt to understand the concept and the manifestation of the sacred space found in Romo Mangunwijaya’s churches in accordance to the concept and the manifestation of the Catholic Church’s sacred space.Research will be carried out based on a preliminary study conducted by studying the universal sacred space theory proposed by Eliade and the theory of the Catholic Church’s sacred space that refers to the principles of the liturgy space. Results of analysis of each object of the study will then be processed further through a comparison table so that it can be concluded the manifestation of a sacred space in Romo Mangunwijaya’s churches.From the results of research on the objects of the study, showed that the manifestation of the sacred space of the Romo Mangunwijaya’s Churches dominantly shown in terms of orientation, ornaments, and atmosphere. In addition, the case study that shows the most dominant manifestation of the sacred space is Theresia Salam Church.The benefits of this research are: for general public, this research can improve the knowledge of the importance of the sacred space within the Catholic Church and how to integrate local values and culture into the sacred space concept established in the Catholic Church's rules. Meanwhile, for the architects and institutions of the Catholic Church, this research can improve the knowledge of the concept of sacred space in the Catholic Church and how to manifest the concept of the sacred space into the architecture of the Catholic Church. Key Words: sacred space, church, Y.B. Mangunwijaya